Respuesta :
x is the first number
y is the second number
z is the third number
Given
x + y + z = 6 (The sum of three numbers is 6)
z = x + y (the third number is the sum of the first and second numbers)
x = z + 1 (the first number is one more than the third number)
x + y + z=6
z + z = 6 (because z = x + y)
2 z = 6
Divide both sides by 2 then
z = 3
Replace z = 2 into x = z+1 to find x
x = 3 + 1
x = 4
Replace x = 4 , z = 3 into z = x + y to find y
3 = 4 + y
Subtract 4 to both sides
3 - 4 = 4 + y -4
Simplify
-1 = y or y = -1
Answer x = 4, y = -1, z = 3
Proof:
x + y + z = 6 (The sum of three numbers is 6)
4 + (-1) + 3 = 6
6 = 6
z = x + y (the third number is the sum of the first and second numbers)
3 = 4 + (-1)
3 = 3
x = z + 1 (the first number is one more than the third number)
4 = 3 + 1
4 = 4
y is the second number
z is the third number
Given
x + y + z = 6 (The sum of three numbers is 6)
z = x + y (the third number is the sum of the first and second numbers)
x = z + 1 (the first number is one more than the third number)
x + y + z=6
z + z = 6 (because z = x + y)
2 z = 6
Divide both sides by 2 then
z = 3
Replace z = 2 into x = z+1 to find x
x = 3 + 1
x = 4
Replace x = 4 , z = 3 into z = x + y to find y
3 = 4 + y
Subtract 4 to both sides
3 - 4 = 4 + y -4
Simplify
-1 = y or y = -1
Answer x = 4, y = -1, z = 3
Proof:
x + y + z = 6 (The sum of three numbers is 6)
4 + (-1) + 3 = 6
6 = 6
z = x + y (the third number is the sum of the first and second numbers)
3 = 4 + (-1)
3 = 3
x = z + 1 (the first number is one more than the third number)
4 = 3 + 1
4 = 4